Teaching & learning guide for: objectionable commemorations: ethical and political issues - Lim, Chong-Ming (2024)
What should we think about commemorative artefacts that honour in appropriate targets? It is often thought that such questions are best left to politics“ on the ground” .This position, however, neglects the many philosophical complications surrounding commemorative artefacts. In this teaching and learning guide, we identify some key texts within the literature, and suggest some ways to integrate them into a course on objectionable commemorations.